IDENTIFICATION OF THE STRUCTURE OF A PROTEIN BY X-RAY CRYSTALLOGRAPHY AND NMR SPECTROSCOPY (The Research of Medical Science Review, 2024)
Proteins are essential macromolecules in living organisms that perform various biological functions. Understanding the protein structure is crucial for elucidating their function and designing a targeted drug. X-ray crystallography and NMR Spectroscopy are the two most commonly used methods for determining the three-dimensional arrangement of proteins. X-ray crystallography is generally more suitable for larger proteins, while NMR spectroscopy is more suitable for smaller proteins. Both methods have benefits and limits, and each method's high quality depends on the protein's size and complexity. In this article, we emphasize how the grouping of X-ray crystallography and NMR spectroscopy delivers special power to identify the structures of complex protein complexes.